Tanshinone IIA delays liver aging by modulating oxidative stress - Liu, Qi; Li, Xu; Luo, Yi (Frontiers in Pharmacology, 2024)
Organ-specific aging is increasingly recognized for its research significance, with liver aging demonstrating particular relevance due to its central role in metabolism. We have pioneered the discovery that the expression of ESRRG in the liver positively correlates with age and have established its association with clinical characteristics, including hepatic edema. Our findings link liver aging to a shift in oxidative stress states, where ESRRG, a crucial nuclear receptor responsive to oxidative stress, may be modulated by various small molecules. Through virtual screening of a natural medicinal molecule database followed by further validation, we confirmed that the natural compound Tanshinone IIA mitigates oxidative stress-induced damage in the liver via the ESRRG/Cyp2e1 pathway, thus decelerating liver aging. Importantly, our study also explores the dynamic impact of Tanshinone IIA on ESRRG conformation, providing a profound understanding of its molecular interactions with ESRRG and laying a foundation for the rational design of small molecules based on natural compounds.